Ms. Mentor's impeccable advice for women in academia - Toth, Emily (Philadelphia University of Pennsylvania Press, 1997)
In question-and-answer form, Ms. Mentor advises academic women about issues they daren't discuss openly, such as: How does one really clamber onto the tenure track when the job market is so nasty, brutish, and small? Is there such a thing as the perfectly marketable dissertation topic? How does a meek young woman become a tiger of an authority figure in the classroomand get stupendous teaching evaluations? How does one cope with sexual harassment, grandiosity, and bizarre behavior from entrenched colleagues?
Ms. Mentor's readers will find answers to the secret queries they were afraid to ask anyone else. They'll discover what it really takes to get tenure; what to wear to academic occasions; when to snicker, when to hide, what to eat, and when to sue. They'll find out how to get firmly planted in the rich red earth of tenure. Ms. Mentor's wisdom grows out of many a real-life experience: she guarantees that some readers will squirm. She lavishly dispenses witty advice, and valuable information, while despising psychobabble, postcomprehensible jargon, and pontification by anyone other than herself. She also insists that sisterhood is, and must be, powerful. Readers of Ms. Mentor's Impeccable Advice for Women in Academia are in for an unusual treat.
Graduate school: the rite of passage -- Job hunt -- Conference scene -- First year on the job -- Perils and pleasures of teaching -- When cultures collide -- Muddles and puzzles -- Slouching toward tenure -- Post-tenure -- Emerita: the golden years.
Includes bibliographical references (p. 209-215) and index.
Keywords: Women college teachers -- United States -- Miscellanea; Women graduate students -- United States -- Miscellanea; Women college teachers -- United States -- Social conditions; Women graduate students -- United States -- Social conditions; Women college teachers -- United States -- Conduct of life; Women graduate students -- United States -- Conduct of life